UTILIZATION OF WOOD WASTE AND REJECTED PALM OIL SEEDS FOR ROCKET STOVE FUEL AS AN ALTERNATIVE TO LPG GAS IN PETUK LITI VILLAGE, CENTRAL KALIMANTAN - Cassiophea, Lola; Revianti Coenraad; Ni Putu Diah Agustin Permanasuri; Tuah; Danar Airangga Windra Gautama; Mega Kurniawati; Ruslan; Sri Wahyuni (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2024)
This service activity aims to explore the potential for utilizing wood waste and rejected palm kernels as alternative fuel for rocket stoves in Petuk Liti Village, Pulang Pisau Regency, Central Kalimantan. The background to this research is the urgent need for alternative energy sources that are cheaper and environmentally friendly, considering the increasing price of LPG gas and the limited access of rural communities to reliable energy sources. Utilizing wood waste and rejected palm kernels as fuel not only offers an economical solution, but also helps in waste management and reducing carbon emissions, which is in line with sustainable development goals. This service involves several important stages, starting from collecting and processing raw materials, developing and testing stoves, as well as the economic and environmental benefits of using alternative fuels. It is hoped that this activity can be implemented more widely in other areas that have limited access to conventional energy, as well as supporting the government's efforts to achieve national energy security and reduce carbon emissions. The output target of this service is to make a significant contribution to the development of renewable energy technology based on local resources, as well as providing a more environmentally friendly and economical alternative for the people of Petuk Liti Village.